KEPUASAN WISATAWAN TERHADAP ATRIBUT DESTINASI WISATA DI THE NUSA DUA BALI - Sari, Ni Putu Ratna; Suarka, Fanny Maharani; Sulistyawati, Agung Sri; Kusumadewi, Putu Diah (Jurnal Master Pariwisata (JUMPA); Volume 09, Nomor 02, Januari 2023DO - 10.24843/JUMPA.2023.v09.i02.p09, 2023)
This research was conducted at The Nusa Dua Bali. This area was a luxury area managed by ITDC. The decrease in the number of tourist visits to The Nusa Dua needed to be further studied regarding tourist satisfaction during the Covid 19 pandemic so that later it could be utilized as the input for consideration in determining the direction of regional development of the Nusa Dua in the future and making The Nusa Dua an area that continued to exist as the best area with high quality. This study aimed to: 1) Know the characteristics of tourists staying at The Nusa Dua, 2) Analyze the level of tourist satisfaction with the attributes of The Nusa Dua tourist destinations. The data analysis technique utilized was the Important Performance Analysis (IPA) with a sample of 250 tourists. Results of this research showed that the characteristics of tourists stayed in The Nusa Dua were dominantly (51.6%) male, 42.8% were aged between 25-34 years old, 87.6% were Indonesian citizen, 57.6% were self-employed. 57.6% have stayed more than once, 76.4% stayed with length of stay 1-5 days, 46.4% traveling with friends and family, 46% used online booking, 76% purposed of visit destination was for holidays, 38.4% sources of information for the visit were taken from the previous one. The level of tourist satisfaction with the attributes of The Nusa Dua destination was 100.06%, so that in general it could be said that tourists were very satisfied with The Nusa Dua. Keywords: guest satisfaction; destination attributes; important performance analysis; The Nusa Dua